PERANAN KEPEMIMPINAN DI DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI KALIMANTAN BARAT - Millina Fatma (FISIP Universitas Tanjungpura, 2013)
This article is intended to determine the extent of a leadership role in empowering the employees in terms of placement, development, utilization and maintenance personnel, the location of the research done at the Department of Culture and Tourism of West Kalimantan province with a lot of reasons staffing problems-problems that the authors deem appropriate to in carefully. In this study, using qualitative descriptive study. The results of this study are: the staffing, already refers to professionalism but still not up and still not considered career preparation, while in the administration of employee development, implementation and intensity of participation of employees in training are not sufficient, however, has been given the opportunity of formal education increased employee although not so optimal, in the implementation and maintenance of employee utilization in terms of the implementation of the division of tasks and workload of employees have not been effective and optimal implementation, but in motivating employees is implemented well. From these results it is recommended that as a leader in empowering employees who should have a high commitment to undertake serious efforts and always pay attention to careers and professionalism in staffing, employee development, and always pay attention to the use and maintenance employees. Keywords: Empowerment, Placement, Development, Utilization and Maintenance Employees.